2020
DOI: 10.2147/ott.s260499
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Hsa-MiR-590-3p</em> Promotes the Malignancy Progression of Pancreatic Ductal Carcinoma by Inhibiting the Expression of p27 and PPP2R2A via G1/S Cell Cycle Pathway</p>

Abstract: Objective To investigate the effect of miR-590-3p on the malignant biological behavior of pancreatic cancer, and to explore the target genes and pathways directly affected by miR-590-3p , to provide new therapeutic ideas and targets for the study of the diagnosis and treatment of pancreatic cancer. Methods We used qRT-PCR to measure miR-590-3p expression quantities. We used cell cycle, CCK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The hsa-mir-590-3p is an important target in the TF-miRNA co-regulatory network. Previous studies have reported that the hsa-mir-590-3p may play a significant role in pancreatic cancer [ 54 ], colorectal cancer [ 55 ], prostate cancer [ 56 ], and also breast cancer [ 57 ] as a therapeutic biomarker. No study has yet reported that hsa-mir-590-3p may play any role in OC.…”
Section: Discussionmentioning
confidence: 99%
“…The hsa-mir-590-3p is an important target in the TF-miRNA co-regulatory network. Previous studies have reported that the hsa-mir-590-3p may play a significant role in pancreatic cancer [ 54 ], colorectal cancer [ 55 ], prostate cancer [ 56 ], and also breast cancer [ 57 ] as a therapeutic biomarker. No study has yet reported that hsa-mir-590-3p may play any role in OC.…”
Section: Discussionmentioning
confidence: 99%
“…The hsa-mir-590-3p is an important target in the TF-miRNA co-regulatory network. Previous studies have reported that the hsa-mir-590-3p may play a significant role in pancreatic cancer [54], colorectal cancer [55], prostate cancer [56], and also breast cancer [57] as a therapeutic biomarker. There is no study that has been exposed yet that hsa-mir-590-3p may play any role in OC.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences found that many miRNAs associated with the cryopreservation of sperm in mammals are related with fertility, the development of early embryo, and pregnancy. Among the 11 DEmiRs that we identified in human frozen-thawed sperm, hsa-miR-106b-5p ( Wei et al, 2017 ; He et al, 2020 ), hsa-miR-590-3p ( Shi X. et al, 2020 ), hsa-miR-328-3p ( Bai et al, 2021 ), and hsa-miR-140-5p ( Nie et al, 2019 ; Jiao et al, 2020 ) may cause a decreased fertilization rate in IVF and ICSI cases when using cryopreserved sperm since these miRNAs are all related to cell cycle and mitosis. miR-106b-5p is a key miRNA morula and blastocyst developmental state, having potential interactions with embryo-expressed genes ( Sanchez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%